(untitled) (Journal of Civil Engineering Researchers, 2026)
In groundwater flow modeling, as in any modeling problem, a certain amount of error is inevitable. In groundwater flow and contaminant transport modeling, recharge and discharge wells act as point sources or sinks. How these wells are treated can influence accuracy and reduce uncertainty or increase the amount of error. This study investigates an intelligent aquifer mesh. To illastrate the theory, two hypothetical aquifers with triangular and square elements were examined, in both confined and unconfined conditions. In the intelligent aquifer mesh, after gridding the model domain, pumping or recharge wells are considered as nodes. Consequently, the numbering of nodes and elements are updated accordingly. Groundwater flow modeling is performed on the updated mesh to enhance accuracy. The results of this research indicated that considering the recharge and pumping wells as a node and re-gridding the model area can perform groundwater flow modeling with more accuracy and ultimately the results will be more reliable.